SELEKSI JENIS PADI (Oryza sativa, L) TERHADAP CEKAMAN KEKERINGAN AKIBAT PEMBERIAN SENYAWA PEG (POLYETILENA GLIKOL) 6000 PADA FASE PERKECAMBAHAN - Nazirah, Laila (Agros Journal of Agriculture Science, 2024)
This research aims to determine the effect of the growth of rice (Oryza sativa, L) on checking drought due to the administration of PEG (Polyethylene Glycole) 6000 compounds in the germination phase and to determine the combination of types of rice and the concentration of PEG 6000 compounds on the growth of rice plants. The materials used in the research were rice seeds G1 = Mustakmal 5, G2 = Inpari 32, G3 = CBD, G4 = Inpari 78, G5 = MR 4, G6 = Mokonga, PEG (Polyethylene Glycole) 6000 10% and 25%, filter paper, distilled water. Such as tools used are rulers, analytical scales, label paper, stationery, calculators, cameras, buckets, petri dishes, measuring cups, tweezers, baskets, 500 ml measuring flasks, spatulas, plastic crabs, auto meter set counters, stirrers, and tools other supporters. The results of this research show that there is an interaction between factors between several types of rice with the use of PEG 6000 Compound in the variable of giving 0% PEG 6000 with the mustakmal rice type (G1) which is the best combination treatment for the observed variables of plumule length and root length. The mustakmal rice type (G1) is the best type for the observed variables of plumule length, root length and tolerance index. The use of PEG 6000 at a concentration of 0% (P1) is the best provision for observing variables plumule length, root length, plumule-radicle length ratio and tolerance index. Keywords: water stress, types of rice, PEG 6000 INTISARIPenelitian ini bertujuan untuk pengaruh pertumbuhan jenis padi (Oryza sativa, L) terhadap cekaman kekeringan akibat pemberian senyawa PEG (Polyethylene Glycole) 6000 pada fase perkecambahan serta mengetahui kombinasi antara jenis-jenis padi dan konsentrasi senyawa PEG 6000 terhadap pertumbuhan tanaman padi. Bahan yang di gunakan dalam penelitian adalah benih padi benih G1 = Mustakmal 5, G2 = Inpari 32 , G3 = CBD , G4 = Inpari 78, G5 = MR 4, G6 = Mokonga, PEG ( Polyethylene Glycole ) 6000 10% dan 25%,  kertas saring, aquades. Adapun alat yang digunakan pengaris, timbangan analitik, kertas lebel, alat tulis, kalkulator, kamerah, ember, cawan petri, gelas ukur, pinset, keranjang, labu ukur 500 ml, spatula, plastik crab, auto metic set counter, stirrer, dan alat pendukung lainnya. Hasil penelitian ini menunjukkan adanya kombinasi antar faktor beberapa jenis padi dengan penggunaan Senyawa PEG 6000 pada variable pemberian PEG 6000 10% dengan jenis padi mustakmal (G1) merupakan perlakuan kombinasi terbaik pada variable pengamatan panjang plumula dan panjang akar. Jenis padi mustakmal (G1) merupakan jenis terbaik pada variable pengamatan panjang plumula, panjang akar dan indeks toleransi. Penggunaan PEG 6000 pada konsentrasi 10% (P2) merupakan pemberian terbaik pada variable pengamatan panjang plumula, panjang akar, rasio panjang plumula-radikula dan indeks toleransi. Kata Kunci : cekaman air, Jenis Padi, PEG 6000